Implementing network protocols at user level. - Thekkath, Chandramohan A.
Traditionally, network software has been structured in a monolithic fashion with all protocol stacks executing either within the kernel or in a single trusted user-level server. This organization is motivated by performance and security concerns. However, considerations of code maintenance, ease of debugging, customization, and the simultaneous existence of multiple protocols argue for separating the implementations into more manageable user-level libraries of protocols. This paper describes the design and implementation of transport protocols as user-level libraries.We begin by motivating the need for protocol implementations as user-level libraries and placing our approach in the context of previous work. We then describe our alternative to monolithic protocol organization, which has been implemented on Mach workstations connected not only to traditional Ethernet, but also to a more modern network, the DEC SRC ANI. Based on our experience, we discuss the implications for host-network interface design and for overall system structure to support efficient user-level implementations of network protocols.
Keywords: Computer systems organization; Computer communication networks; Network protocols; Protocol architecture (OSI model).; Network architecture and design; Packet switching networks; Network protocols; TCP IP; Performance of systems; Performance attributes; Design; Performance; Security